2017
DOI: 10.1093/ajh/hpx105
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension and Cardiovascular Risk Profile in a Middle-Income Setting: The HELISUR Study

Abstract: In this first extensive cardiovascular assessment in the general population of this middle-income Caribbean country, high prevalence of hypertension with inadequate levels of treatment and control was predominant. The findings emphasize the need for collaborative effort from national and international bodies to prioritize the implementation of affordable and sustainable public health programs that combat the escalating hypertension and cardiovascular risk factor burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…The Suriname Healthy study and the Healthy Life in Suriname (HeliSur) study have shown that Hindustani and Creole people have high prevalence of CVD risk factors such as DM and HT rates, which is in line with the high prevalence found in our study. 23 , 28 , 29 HF admissions due to IHD were twice as high in patients of Asian descent compared to HF patients of African descent, whereas HHD was more prevalent in HF patients of African descent compared to patients of Asian descent. This is in line with studies, showing that atherosclerotic diseases and IHD are more prevalent in Asian and HHD in Africans.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…The Suriname Healthy study and the Healthy Life in Suriname (HeliSur) study have shown that Hindustani and Creole people have high prevalence of CVD risk factors such as DM and HT rates, which is in line with the high prevalence found in our study. 23 , 28 , 29 HF admissions due to IHD were twice as high in patients of Asian descent compared to HF patients of African descent, whereas HHD was more prevalent in HF patients of African descent compared to patients of Asian descent. This is in line with studies, showing that atherosclerotic diseases and IHD are more prevalent in Asian and HHD in Africans.…”
Section: Resultsmentioning
confidence: 89%
“…21 CVD is the major cause of death (28%) and several studies on CVD risk factors prevalence in Suriname, have shown a high and rising prevalence of these risk factors. 22 , 23 , 24 , 25 , 26 , 27 The Suriname Health Study, for instance, demonstrated a prevalence of 26% for HT, 14% for DM and approximately 30% of people between 55 and 64 years of age with three or more CVD risk factors. 28 , 29 This high prevalence of risk factors may result in a high CVD and HF burden.…”
Section: Introductionmentioning
confidence: 99%
“…We recently reported the prevalence of hypertension, obesity, diabetes, and dyslipidemia in Paramaribo, Suriname: respectively 39.5%, 36.8%, 14.5%, and 40.9% . The sample size calculation was based on the lowest prevalence (ie, diabetes) and we calculated that at least 690 women were needed to assess a difference in these risk factors with α = .05 and 1‐β = .80 using multivariable logistic regression analysis with 10 other predictors.…”
Section: Methodsmentioning
confidence: 99%
“…Suriname is a Caribbean nation with approximately 560,000 citizens who are mainly of African or Asian (South Asian, Indonesian, and Chinese) ancestry. More than 70% of the population lives in an urban setting [7–12]. The gross national income per capita (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Diseases of the circulatory system are the main cause of death [7, 10]. The Healthy Life in Suriname (HeliSur) study was the first major scientific study, conducted from 2014 to 2017 in a random sample of the urban population, designed to assess cardiovascular risk factors as well as asymptomatic and symptomatic target organ damage including CKD.…”
Section: Methodsmentioning
confidence: 99%